Association between serum 25-hydroxyvitamin D levels and Early Vascular Aging in young and middle-aged adults - Jinpeng Cong; Rui Hu; Jinyan Ren; Xinfeng Wang; Na Li; Ying Sun (PLoS ONE, 2026)
Background Cardiovascular disease (CVD) remains the leading cause of mortality and morbidity worldwide. Early vascular aging (EVA) is an independent predictor of cardiovascular risk in young and middle-aged adults. The plausible association between EVA and vitamin D warrants further investigation. Methods This study examined the relationship between serum 25-hydroxyvitamin D [25(OH)D] levels and EVA in young and middle-aged healthy adults.This cross-sectional study included 2047 eligible participants who underwent physical examinations at the Health Management Center of the Affiliated Hospital of Qingdao University between May 2023 and May 2025. Participants were categorized into EVA group (n = 687) and control group (n = 1360) based on brachial ankle pulse wave velocity (baPWV). Logistic regression and restricted cubic splines assessed the association between 25(OH)D and EVA, with an inflection point identified using two-piecewise linear regression. Subgroup analyses and interaction tests were conducted by age, sex, blood collection month, smoking status, alcohol drinking status, hypertension, diabetes, and body mass index (BMI). Results The prevalence of EVA was 33.56%. Each 10 ng/mL increase in 25(OH)D was associated with a 19% decrease in the likelihood of EVA (OR = 0.81, 95% CI: 0.70–0.94, P = 0.008).Compared with Q1, Q4 had a significantly lower risk (OR = 0.55, 95% CI: 0.40–0.76, P < 0.001), while Q2 and Q3 did not differ (both P > 0.05). Restricted cubic spline analysis showed a nonlinear L-shaped association (P for non linearity = 0.015) with a threshold at 17.90 ng/mL: below this level, higher 25(OH)D was linked to a lower EVA risk (OR=0.90，95%CI: 0.85–0.96), whereas no significant association was observed above it. Subgroup analyses indicated a particularly significant inverse association between 25(OH)D levels and EVA in men and overweight/obese individuals. Significant interactions were observed for sex, BMI, and age (all P < 0.05), while interactions with other factors, such as blood collection month, hypertension, diabetes, smoking status, drinking status were not statistically significant. Conclusion This study suggests an inverse association between 25(OH)D levels and EVA, with a more pronounced association possibly observed in men and individuals with overweight/obesity, and further indicates a threshold at 17.9 ng/mL below which this inverse association is significantly enhanced.